2020
DOI: 10.1177/2399808320924433
|View full text |Cite
|
Sign up to set email alerts
|

Understanding commuting patterns and changes: Counterfactual analysis in a planning support framework

Abstract: In order to contain commuting distance growth and relieve traffic burden in mega-city regions, it is essential to understand journey-to-work patterns and changes in those patterns. This research develops a planning support model that integrates increasingly available mobile phone data and conventional statistics into a theoretical urban economic framework to reveal and explain commuting changes. Base-year calibration and cross-year validation were conducted first to test the model’s predictive ability. Counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…A plethora of research has evidenced that mental disorders are associated with environmental changes [16][17][18]. According to a self-assessed mental health survey, Xue et al [16] reported that an increase in air pollution is associated with a higher probability of self-assessed mental health problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A plethora of research has evidenced that mental disorders are associated with environmental changes [16][17][18]. According to a self-assessed mental health survey, Xue et al [16] reported that an increase in air pollution is associated with a higher probability of self-assessed mental health problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It supplements decades of PSS literature presenting novel approaches to core model development (Basu andFerreira, 2020: 1397;Jia et al, 2020Jia et al, : 1418 with an increasing focus on the integration of the planning process and the applications of PSS technologies (Jiang et al, 2020(Jiang et al, : 1343Page et al, 2020Page et al, : 1508. User interface developments are also presented (Pettit et al, 2020(Pettit et al, : 1490Yang et al, 2020Yang et al, : 1474 as are urban analytics that utilize recently available big data sets (Pan et al, : 1456Yang, 2020Yang, : 1440. These additions help demonstrate new opportunities for the integration of planning support research, urban informatics, and smart cities.…”
Section: Discussionmentioning
confidence: 99%
“…Instrumental value is produced by enabling feedback solicited from planners and local stakeholders directly implicate PSS model outcomes and improvements (Cai et al, 2020(Cai et al, : 1380Pettit, 2020Pettit, : 1490Page et al, 2020Page et al, : 1508. Planner and stakeholder inputs help to create multiple scenarios that can inform planning consequences and policy decisions (Yang, 2020(Yang, : 1440Yang et al, 2020Yang et al, : 1474Xu et al, 2020Xu et al, : 1361. The normative value of participation is realized in the smart city ideal of transparent, participatory, and collaborative open government and data (Deal et al, 2017b;Pereira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study stated that if parents use cars or motorcycles for their commuting trips, the likelihood of taking their children to school by private vehicles increases [28]. Meanwhile, Yan found that journey-to-work patterns significantly influence the mode choice decision in Shanghai [29]. Lin and Chang also stated that when the location of the children's school is close to parents' offices or located along the parent's travel route, parents tend to escort their children to school by private vehicle on the way to the workplace [30].…”
Section: Introductionmentioning
confidence: 99%